Modelo sociocognitivo, pragmalingüístico y didáctico para la producción de textos escritos - GRUPO DIDACTEXT (Didáctica del Texto), GRUPO DIDACTEXT (Didáctica del Texto) (Didáctica. Lengua y Literatura, 2003)
This work examines the preparation of a model for production of written texts. It is based on Hayes’ (1996) proposal and it considers the gaps that he himself points out in his introduction. The model prepared by Didactext, is conceived from the interaction of three dimensions symbolized by reoccurring concentric circles. The first circle corresponds to the cultural environment, or each one of the spheres of the human praxis in which the creator of any written work is immersed. The second circle refers to the production contexts, which include the social, situational and the physical contexts, the audience and composition media. The third circle corresponds to the individual. It considers the role of memory in the production of a text from the sociocultural focus, motivation and emotions, and cognitive and metacognitive strategies. Within these strategies, four functional units that work concurrently are conceived: access to knowledge, planning, production of text and revision